Periplaneta americana Extract Pretreatment Alleviates Oxidative Stress and Inflammation and Increases the Abundance of Gut Akkermansia muciniphila in Diquat-Induced Mice - Shiyi Lu; Shuyi Xu; Lingjun Chen; Yuhang Deng; Jie Feng (MDPI AG, 2022)
Studies have shown that Periplaneta americana extract (PAE) has good therapeutic effects in inflammatory disorders such as ulcerative colitis, alcoholic hepatitis, and gastric ulcers. However, whether or not PAE has good pre-protective effects has not been widely and deeply studied. In this study, we investigated the effects of PAE pretreatment for 7 days on oxidative stress and inflammation triggered by oxidative stress by using diquat-induced C57BL/6 mice as an oxidative stress model. The results showed that PAE pretreatment could significantly reduce oxidative stress in the intestine and liver by reducing the production of MDA, and improved antioxidant systems (SOD, CAT, GSH, and T-AOC). By primarily activating the anti-inflammatory cytokine (IL-10) mediated JAK1/STAT3 signaling pathway, PAE also effectively reduced oxidative stress-induced liver inflammation while also reducing liver damage, as evidenced by the reductions in serum AST and ALT. PAE pretreatment also had a significant effect on maintaining the intestinal barrier function, which was manifested by inhibiting a decrease in the expression of tight junction proteins (ZO-1 and occludin), and reducing the increased intestinal permeability (serum DAO and D-Lac) caused by diquat. The 16S rRNA sequencing analysis revealed that diquat decreased the gut microbiota diversity index and increased the abundance of pathogenic bacteria (e.g., Allobaculum, Providencia and Escherichia-Shigella), while PAE pretreatment responded to diquat-induced damage by greatly increasing the abundance of Akkermansia muciniphila. These findings elucidate potential pre-protective mechanisms of PAE in alleviating oxidative stress and inflammation, while providing a direction for the treatment of metabolic diseases by utilizing PAE to enhance the abundance of gut A. muciniphila.